Parental Knowledge Overview of the Negative Impact of Gadgets for School-Age Children in RT 02 Kampung Tenun Village, Samarinda Seberang - Ruminem Ruminem; Sunartiningsih Sunartiningsih; Rita Puspa Sari (Jurnal Kesehatan Pasak Bumi Kalimantan, 2020)
Backgoround: One of the most developed communication tools at the moment is the gadget. In general every day children today use gadgets, it is advisable that those children operating gadget should get control from parents because the excessive use of gadget can give negative impact for them. Therefore, every parent should know the negative impact of gadget on children. The purpose of this research is to know the level of knowledge of parents on the negative impact of gadget on school aged children in the Neighbourhood Ward 02 of Kampung Tenun District - Samarinda Seberang. Research methods : The type of this research is descriptive Quantiatif. Population is parents who have school age children The samples amount 30 parents of school age children and purposive technique sampling was also used. The instrument to collect the data was questionnaire. Univariate data analysis. The result of this research showed that of the 30 respondents, 11 people (37%) have good knowledge, 9 people (30%) have fair knowledge, and 10 people (33%) have low knowledge. Conclucion : Therefore, it can be concluded that there are many respondents having low level of knowledge so it is expected that parents improve their knowledge by looking for information related to the negative impact of gadget on school aged children as well as to prevent the negative impact it self.Keywords: Knowledge, Negative Impact of Gadget, School Age Children